2009 IFIP/IEEE International Symposium on Integrated Network Management 2009
DOI: 10.1109/inm.2009.5188864
|View full text |Cite
|
Sign up to set email alerts
|

Self-management of hybrid networks: Can we trust netflow data?

Abstract: Network measurement provides vital information on the health of managed networks. The collection of network information can be used for several reasons (e.g., accounting or security) depending on the purpose the collected data will be used for. At the University of Twente (UT), an automatic decision process for hybrid networks that relies on collected network information has been investigated. This approach, called selfmanagement of hybrid networks requires information retrieved from measuring processes in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Our validation showed high accuracy for both size and duration of high-rate, large-sized flows for selected thresholds [8]. Our algorithm for size/duration computation is similar to that used by Fioreze et al [7] with one difference. We aggregate records into flows for only those flows that had at least one NetFlow record in which a size threshold of 1 GB was exceeded (since size computation from sampled NetFlow records is not accurate for smaller-sized/lower-rate flows).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Our validation showed high accuracy for both size and duration of high-rate, large-sized flows for selected thresholds [8]. Our algorithm for size/duration computation is similar to that used by Fioreze et al [7] with one difference. We aggregate records into flows for only those flows that had at least one NetFlow record in which a size threshold of 1 GB was exceeded (since size computation from sampled NetFlow records is not accurate for smaller-sized/lower-rate flows).…”
Section: Introductionmentioning
confidence: 57%
“…Solution approach: Prior work has shown that NetFlow data can be used to accurately determine the size of large-sized, high-duration flows even with 1-in-1000 packet sampling rates though duration accuracy was reported to be lower [7]. Our validation showed high accuracy for both size and duration of high-rate, large-sized flows for selected thresholds [8].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…As a result of sampling, the collected network traffic is an estimation rather than the real traffic. Our goal in this section is to observe whether the use of sampling on elephant flows may inaccurately report our metrics of interest, namely number of bytes, number of packets, and duration [54]. These metrics are needed to calculate Bps and Pps throughputs.…”
Section: The Effects Of Sampling On Elephant Flowsmentioning
confidence: 99%
“…Fioreze et al [52] proposed redirecting elephant flows (which they defined as long in duration and big in volume) to optical circuits in hybrid IP/optical networks. The focus of this work was on evaluating the impact of sampling rates.…”
Section: Related Workmentioning
confidence: 99%